"Dark" Singlet Oxygen Made Easy. Issue 54 (20th August 2019) - Elsherbini, Mohamed; Allemann, Rudolf K.; Wirth, Thomas
Abstract: An operationally simple continuous flow generator of "dark" singlet oxygen has been developed. The singlet oxygen was efficiently reacted with several chemical traps to give the corresponding oxygenated products in high yields. The developed "dark" singlet oxygen generator has been successfully applied in the synthesis of the antimalarial drug artemisinin. Abstract : An efficient and easy generation of "dark" singlet oxygen allows the straightforward oxygenation of various organic substrates. A simple flow setup allows the precise control of mild reaction conditions (see scheme).